Post-Cutting Hot Water Treatment of Pepper Fruit: Impact on Quality During Short-Term Storage - Maria Grzegorzewska; Aleksandra Machlańska (Agronomy)
Fresh-cut vegetables are gaining economic importance around the world. They are highly perishable products, and in the context of global food waste challenges, any new solutions to reduce losses are in line with the expectations of producers, traders, and consumers. The aim of this study was to evaluate the effect of hot water treatment (HWT) on the quality and durability of two varieties of fresh-cut peppers at three storage temperatures: 3, 5, and 8 °C. Microscopic observations revealed changes in the tissue structure of the pepper sticks. During the storage of red-fruit “Yecla” peppers, the HWT samples retained better firmness. The peppers treated at 55 °C for 12 s maintained the best quality during storage. Cream-fruit “Blondy” peppers softened during storage, but the browning of the cut surface contributed the most to the reduction in quality. HWT at 53 °C for 3 min or 50 °C for 5 min effectively inhibited the development of destructive changes during storage. HWT is beneficial for fresh-cut peppers, but the temperature and duration of operation should be properly selected given the nature of the cultivar.